а) при x = -6
x²/2 - x/3 = 36/2 - (-6/3) = 18 + 2 = 20
при х = -1
x²/2 - x/3 = (-1)²/2 - (-1/3) = 1/2 + 1/3 = 5/6
при х = 0
x²/2 - x/3 = 0²/2 - 0/3 = 0 - 0 = 0
при х = 1
x²/2 - x/3 = 1²/2 - 1/3 = 1/2 - 1/3 = 1/6
при x = 2
x²/2 - x/3 = 2²/2 - 2/3 = 4/2 - 2/3 = 2 - 2/3 = 4/6 = 2/3
б) при x = -6
2x³ + x/2 = 2 · (-6)³ + (-6/2) = -432 - 3 = -435
при х = -1
2x³ + x/2 = 2 · (-1)³ + (-1/2) = -2 - 0,5 = -2,5
при х = 0
2x³ + x/2 = 2 · 0³ + 0/2 = 0 + 0 = 0
при х = 1
2x³ + x/2 = 2 · 1³ + 1/2 = 2 + 0,5 = 2,5
при х = 2
2x³ + x/2 = 2 · 2³ + 2/2 = 16 + 1 = 17
а)![\frac{x^{2}}{2}-\frac{x}{3}](/tpl/images/0004/3439/233fa.png)
при x=-6;![\frac{(-6)^{2}}{2}-\frac{(-6)}{3}=\frac{36}{2}+\frac{6}{3}=18+2=20](/tpl/images/0004/3439/041fd.png)
при x=-1;![\frac{(-1)^{2}}{2}-\frac{(-1)}{3}=\frac{1}{2}+\frac{1}{3}=\frac{3+2}{6}=\frac{5}{6}](/tpl/images/0004/3439/c9605.png)
при х=0;![\frac{0^{2}}{2}-\frac{0}{3}=0-0=0](/tpl/images/0004/3439/ae0dc.png)
при х=1;![\frac{1^{2}}{2}-\frac{1}{3}=\frac{1}{2}-\frac{1}{3}=\frac{3-2}{6}=\frac{1}{6}](/tpl/images/0004/3439/9dbcf.png)
при х=2;![\frac{2^{2}}{2}-\frac{2}{3}=\frac{4}{2}-\frac{2}{3}=2-\frac{2}{3}=\frac{6-2}{6}=\frac{4}{6}=\frac{2}{3}](/tpl/images/0004/3439/c2763.png)
б)![2x^{3}+\frac{x}{2}](/tpl/images/0004/3439/8a464.png)
при x=-6;![2\cdot(-6)^{3}+\frac{(-6)}{2}=2\cdot(-216)-\frac{6}{2}=-432-3=-435](/tpl/images/0004/3439/de4b9.png)
при x=-1;![2\cdot(-1)^{3}+\frac{(-1)}{2}=2\cdot(-1)-\frac{1}{2}=-2-0,5=-2,5](/tpl/images/0004/3439/6b39d.png)
при х=0;![2\cdot0^{3}+\frac{0}{2}=0+0=0](/tpl/images/0004/3439/e557b.png)
при х=1;![2\cdot1^{3}+\frac{1}{2}=2\cdot1+\frac{1}{2}=2+0,5=2,5](/tpl/images/0004/3439/0b629.png)
при х=2;![2\cdot2^{3}+\frac{2}{2}=2\cdot8+1=16+1=17](/tpl/images/0004/3439/7822e.png)